Significance of Most-Favoured-Nation terms in global trade: A comprehensive analysis - Tomasz Gonciarz; Thomas Verbeet (World Trade Organization (WTO), 2025)
The Most-Favoured-Nation (MFN) principle has historically been instrumental in promoting stability and equitable trade conditions. In recent decades there has been a rise in bilateral and regional trade agreements, which deviate from the MFN principle in providing more favourable tariff treatment to specific partners. At the same time, WTO Members can, under certain circumstances, raise trade barriers against imports for different reasons, including to counter unfair trade practices. Using a novel and comprehensive dataset based on customs data submitted by WTO Members to the WTO's Integrated Database and complemented by other sources, this paper provides an in-depth analysis of global merchandise trade flows under both MFN and preferential tariffs. The methodology takes into account trade remedies, including anti-dumping and countervailing duties, additional duties in the US and China, and the utilization of trade preferences by incorporating preferential tariffs and bilateral trade flows for 184 economies. The research highlights the nuanced effects of MFN trade across different economies, regions, product and income groups, and compares MFN treatment on imports and exports. The paper concludes that more than 80% of global trade in goods is conducted on MFN terms and underscores the continued importance of the multilateral framework for the global trading system.
Keywords: F13; F14; F15; F53; 330; World Trade Organization; International Trade; Most-Favoured-Nation; Regional Trade Agreements; Preferential Trade Arrangements; Preference Utilization; Trade remedies; Antidumping and Countervailing Duties